2016
DOI: 10.1007/s40261-016-0386-y
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Interaction Studies Between Lesinurad, a Selective Urate Reabsorption Inhibitor, and Major Liver or Kidney Transporters

Abstract: Background and ObjectivesLesinurad is a selective uric acid reabsorption inhibitor (SURI) under investigation for the treatment of gout. This study elucidated the interaction of lesinurad with major liver and kidney transporters in vitro and evaluated the drug–drug interactions (DDIs) of lesinurad and atorvastatin, metformin, and furosemide in clinical studies.MethodsLesinurad interaction with membrane transporters was evaluated in validated transporter-expressing cell systems and analyzed by liquid scintillat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…Because of the contribution of OATP1B1, repaglinide is a suitable CYP2C8 probe if OATP1B1 is not inhibited by the coadministered drug. A previous clinical study suggested that lesinurad does not inhibit OATP1B1 clinically based on the lack of effect on atorvastatin exposure following a single dose of lesinurad . The single‐dose phase of the study with lesinurad and repaglinide showed an increase (31%) in AUC of repaglinide consistent with inhibition of CYP2C8 by lesinurad, and no change in exposure was observed (90% confidence interval between 80% and 125%) following repeated lesinurad dosing.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Because of the contribution of OATP1B1, repaglinide is a suitable CYP2C8 probe if OATP1B1 is not inhibited by the coadministered drug. A previous clinical study suggested that lesinurad does not inhibit OATP1B1 clinically based on the lack of effect on atorvastatin exposure following a single dose of lesinurad . The single‐dose phase of the study with lesinurad and repaglinide showed an increase (31%) in AUC of repaglinide consistent with inhibition of CYP2C8 by lesinurad, and no change in exposure was observed (90% confidence interval between 80% and 125%) following repeated lesinurad dosing.…”
Section: Discussionmentioning
confidence: 84%
“…A previous clinical study suggested that lesinurad does not inhibit OATP1B1 clinically based on the lack of effect on atorvastatin exposure following a single dose of lesinurad. 19 The single-dose phase of the study with lesinurad and repaglinide showed an increase (31%) in AUC of repaglinide consistent with inhibition of CYP2C8 by lesinurad, and no change in exposure was observed (90% confidence interval between 80% and 125%) following repeated lesinurad dosing. Potential explanations for the apparent shift in repaglinide exposure after single-dose versus multiple-dose lesinurad (inhibition and no effect, respectively) may include: random day-to-day variability in the extent of interaction; the possibility that weak induction of CYP2C8 by lesinurad after multiple dosing may offset the weak inhibition observed following a single dose, resulting in no net change in repaglinide exposure; or induction of CYP3A4 by lesinurad, as repaglinide metabolism has a minor component mediated by CYP3A4.…”
Section: Discussionmentioning
confidence: 87%
“…As a positive control, each inhibitor (10 μM quinidine, 25 μM quinidine, 5 μM cimetidine, and 10 μM cimetidine for hOCT1, hOCT2, hMATE1, and hMATE2‐K, respectively) was adjusted rather than HCT. The chosen metformin and inhibitor concentrations were based on previous work by Shen et al (). After 10 min of incubation, Hank's solution was removed and the cells were immediately washed with ice‐cold pure Hank's solution.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, Zurampic is approved by US FDA for patients with gout because of the selective uric acid reabsorption inhibition [11]. Zurampic is reported to function through inhibition of urate transporter 1 (URAT1) which mainly responsible for reabsorption of uric acid from the glomerular ultrafiltrate into the epithelial cells of the renal proximal convoluted tubule [12,13]. Therefore, we mainly focused on Zurampic to explore the potential therapeutic effects and possible underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%